Assessment of the vulnerability of sandy coasts to erosion (short and medium term) for coastal risk mapping (Vendée, W France). (15th February 2021) - Audère, Morgane; Robin, Marc
Abstract: This paper presents an assessment of the vulnerability to erosion of sandy coasts of Vendée (W France). The hazard is assessed i) by the long term by measuring the historical evolution of the shoreline between 1950 and 2016 ii) by the short term by measuring the instantaneous retreats due to extreme events. The method applied in this paper is based on the recommendations of a methodological guide for coastal hazards (PPRL Guide: MEDDE, 2014). In the Coastal Risk Prevention Plans (PPRL in French), erosion hazard zone is written as follow: "Lr = 100 Tx + Lmax" with Lr = the width of the hazard zone, Tx = the average annual retreat rate, Lmax = the value of the maximum retreat following an extreme event. We propose the following recommendations like define the parameter Lmax considering more than one storm (with two cases: i) Lothar/Martin (1999) and Xynthia (2010)), ii) make the projection by 2050 instead of 2100 in the PPRL), iii) update the data used to define the erosion hazard zone in the PPRL risk maps. Highlights: A study conducted on 109 km of sandy coastline. The measurement of instantaneous shoreline retreat during the 1999 and 2010 storms. A calculation of the parameter Lmax (retreat due to an extreme event). Information by transects every 20m. Recommendations to improve the erosion hazard strips of the Coastal Risk Prevention Plans.